Attrition from antiretroviral treatment services among pregnant and non-pregnant patients following adoption of Option B+ in Haiti. Issue 1 (1st January 2017) - Domercant, Jean Wysler; Puttkammer, Nancy; Young, Paul; Yuhas, Krista; François, Kesner; Grand'Pierre, Reynold; Lowrance, David; Adler, Michelle
ABSTRACT: Background : Access to antiretroviral therapy (ART) has expanded in Haiti because of the adoption of Option B+ and the revision of treatment guidelines. Retention in care and treatment varies greatly and few studies have examined retention rates, particularly among women enrolled in Option B+. Objective : To assess attrition among pregnant and non-pregnant patients initiating ART following adoption of Option B+ in Haiti. Methods : Longitudinal data of adult patients initiated on ART from October 2012 through August 2014 at 73 health facilities across Haiti were analyzed using a survival analysis framework to determine levels of attrition. The Kaplan–Meier method and Cox proportional hazards regression were used to examine risk factors associated with attrition. Results : Among 17, 059 patients who initiated ART, 7627 (44.7%) were non-pregnant women, 5899 (34.6%) were men, and 3533 (20.7%) were Option B+ clients. Attrition from the ART program was 36.7% at 12 months (95% CI: 35.9–37.5%). Option B+ patients had the highest level of attrition at 50.4% at 12 months (95% CI: 48.6–52.3%). While early HIV disease stage at ART initiation was protective among non-pregnant women and men, it was a strong risk factor among Option B+ clients. In adjusted analyses, key protective factors were older age ( p < 0.0001), living near the health facility ( p = 0.04), having another known HIV-positive household member ( p < 0.0001), having greater body mass index (BMI) ( p < 0.0001), pre-ART counseling ( p < 0.0001), and Cotrimoxazole prophylaxis during baseline ( p < 0.01). Higher attrition was associated with rapidly starting ART after enrollment ( p < 0.0001), anemia ( p < 0.0001), and regimen tenofovir+lamivudine+nevirapine (TDF+3TC+NVP) ( p < 0.001). Conclusions : ART attrition in Haiti is high among adults, especially among Option B+ patients. Identifying newly initiated patients most at risk for attrition and providing appropriate interventions could help reduce ART attrition.